Diagnosis Related Groups of Patients Admitted from an Urban Academic Medical Center to a Virtual Hybrid Hospital-at-Home Program - Maniaci MJ; Cowdell JC; Maita K; Avila FR; Dugani SB; Torres-Guzman RA; Garcia JP; Forte AJ; Paulson MR (Dove Medical Press, 2023)
Michael J Maniaci,1 J Colt Cowdell,1 Karla Maita,2 Francisco R Avila,2 Sagar B Dugani,3 Ricardo A Torres-Guzman,2 John P Garcia,2 Antonio J Forte,2 Margaret R Paulson4 1Division of Hospital Internal Medicine, Mayo Clinic, Jacksonville, FL, USA; 2Division of Plastic Surgery, Mayo Clinic, Jacksonville, FL, USA; 3Division of Hospital Internal Medicine, Mayo Clinic, Rochester, MN, USA; 4Division of Hospital Internal Medicine, Mayo Clinic Health Systems, Eau Claire, WI, USACorrespondence: Michael J Maniaci, Division of Hospital Internal Medicine, Mayo Clinic, 4500 San Pablo Road, Jacksonville, FL, 32224, USA, Tel +1 904-956-0081, Fax +1 904-953-2848, Email Maniaci.Michael@mayo.eduBackground: The diagnosis related group (DRG) is used as an economic patient classification system based on clinical characteristics, hospital stay, and treatment costs. Mayo Clinic's virtual hybrid hospital-at-home program, advanced care at home (ACH), offers high-acuity home inpatient care for a variety of diagnosis. This study aimed to determine the DRGs admitted to the ACH program at an urban academic center.Methods: A retrospective study was performed on all patients discharged from the ACH program at Mayo Clinic Florida from July 6, 2020, to February 1, 2022. DRG data were extracted from the Electronic Health Record (EHR). Categorization of DRG was done by systems.Results: The ACH program discharged 451 patients with DRGs. Categorization of the DRG demonstrated that the most frequent code assigned corresponded to respiratory infections (20.2%), followed by septicemia (12.9%), heart failure (8.9%), renal failure (4.9%), and cellulitis (4.0%).Conclusion: The ACH program covers a wide range of high-acuity diagnosis across multiple medical specialties at its urban academic medical campus, including respiratory infections, severe sepsis, congestive heart failure, and renal failure, all with major complications or comorbidities. The ACH model of care may be useful in taking care of patients with similar diagnosis at other urban academic medical institutions.Keywords: hospital at home, home care, home acute care, diagnosis related group, inpatient prospective payment system